A Method for Improving Renogram Production and Detection of Renal Pelvis using Mathematical Morphology on Scintigraphic Images - Xefteris, S.; Tserpes, K.; Varvarigou, T. (Engineering, Technology & Applied Science Research, 2012)
Dynamic renal scintigraphy is a well-established imaging technique in nuclear medicine, used to detail both the organ’s anatomy and function. However, the quality of the produced scintigrams provides an often unreliable diagnostic tool because of a rather bad signal-to-noise ratio and the fact that in certain occasions the regions of interest are too concentrated making it difficult for physician evaluation. The goal of this paper is to achieve a more accurate production of the renal activity graph, by avoiding the inclusion of image artifacts in the detection process. This is achieved by treating pixels as points in a two-dimensional Euclidean space, and exploiting set-theoretic properties and morphological operators. The evaluation of the method in a number of real patient’s scintigrams obtained in a depth of 5 years, showed that, in the majority of the cases, it is feasible to produce a more accurate renogram, for both kidneys and the renal pelvis region, that was helpful for the interpretation of the findings